Tratamento de queloides usando radioterapia pósoperatória com elétrons: estudo comparativo e randomizado com dois esquemas - Oliveira Júnior, Batista de [UNESP]; Schellini, Silvana Artioli [UNESP]; Lastória, Joel Carlos [UNESP]; Carvalho, Lidia Raquel de [UNESP]; Stolf, Hamilton Ometto [UNESP]; Oliveira, Ana Laura Paludetto de (My University, 2013)
Introduction: While several keloid treatment modalities exist, they all offer disappointing results when performed in isolation. The combination of surgical excision and postoperative irradiation with electron beams is effective in improving the quality of scars and reducing the recurrence rate of the condition. Objective: To assess, on a comparative basis, the prospects for cure, and also side effects in the irradiated areas of two treatment methods using electron beams. Methods: A prospective, comparative and randomized clinical study was carried out at the Faculdade de Medicina de Botucatu-UNESP, in Botucatu (SP), Brazil, between 2008 and 2010. The study included patients who were post-operative after their treatment for the resection of keloids. The study population was divided into groups G1 and G2, having received radiotherapy treatment with electrons from a linear accelerator at 30 Gy/10 fractions and 32 Gy/16 fractions, respectively. The patients were followed up with for 18 months. Results were assessed through the observation of two independent evaluators and the distribution of a questionnaire to study participants. Results: Forty-three patients were investigated (21 in G1 and 22 in G2). 52.4% showed good results in G1, with a recurrence rate of 47.6%. In G2, 91% showed good results, with a 9% recurrence rate. Conclusion:The 32 Gy/16 fractions method was proved to be superior to the 30 Gy/10 fractions method, resulting in a better therapeutic response and fewer side effects.

Introdução: As diversas modalidades de tratamento para queloides isoladamente apresentam resultados desapontadores. O tratamento combinado de excisão cirúrgica e irradiação pós-operatória com elétrons é efetivo para a qualidade da cicatriz e redução da taxa de recidiva. Objetivo: Avaliar comparativamente dois esquemas de tratamento utilizando feixes de elétrons em termos de probabilidade de cura e efeitos colaterais na área irradiada. Métodos: Estudo clínico, prospectivo, comparativo e randomizado, realizado na Faculdade de Medicina de Botucatu (Unesp), no período de 2008 a 2010, incluindo pacientes no pós-operatório imediato de ressecção de queloides, divididos nos grupos G1 e G2 que receberam tratamento radioterápico com elétrons de um Acelerador Linear, 30Gy/10 frações para G1 e 32 Gy/16 frações para G2. O seguimento foi de 18 meses. Os resultados foram avaliados através de observação feita por dois avaliadores independentes e questionário aplicado aos participantes do estudo. Resultados: Fizeram parte do estudo 43 pacientes, 21 no grupo G1 e 22 no grupo G2. No grupo G1 houve 52,4% de bons resultados e 47,6% de recidivas. No grupo G2, 91% de bons resultados e 9% de recidivas. Conclusão: O esquema 32Gy/16 frações é superior ao esquema 30Gy/10 frações, com melhor resposta terapêutica e menos efeitos colaterais.
Keloid treatment using post-operative radiotherapy with electron beams: a comparative randomized study of two methods.
Keywords: Quelóide; Elétrons; Radioterapia